Extended Enterprise Model for PSS Within a Systems Engineering Perspective. Issue 4 (10th January 2020) - Harrat, Mourad; Maleki, Elaheh; Belkadi, Farouk; Bernard, Alain
ABSTRACT: Today, firms are adopting Product‐Service Systems (PSS) business models requiring new designing, producing, and consuming methods. Systems engineering is a promising solution addressing the PSS development and life cycle management complexity. Following this perspective, this paper focuses on organizational capabilities representation as part of the PSS enabling systems. Two UML diagrams propose to clarify the structure and to characterize the collaborative processes behind this virtual organization. The proposed systems engineering based modeling framework functions as a background for the design and management of collaborations along the PSS life cycle.